Statistical approach for modeling Malaysia's gross domestic product - Ho, Wei Chin; Fitrianto, Anwar (IDOSI Publications, 2013)
This study investigates factors which affect Malaysia’s gross domestic product. Stepwise regression has been used to construct the appropriate model. The model is constructed by splitting the data into model building set and validation set. The data splitting shows that the regression model is valid. After the process performing to determine the appropriate regression model, the variables private consumption, exports of goods and services and interest rate have significant contribution to Malaysia’s GDP.